Damage Simulation and Ultrasonic Detection of Asphalt Mixture under the Coupling Effects of Water-Temperature-Radiation - Yong-chun Cheng; Peng Zhang; Yu-bo Jiao; Ye-dan Wang; Jing-lin Tao (Advances in Materials Science and Engineering)
In order to accurately simulate the performance changes of asphalt pavement in the hot rainy days, laboratory water-temperature-radiation cycle test is designed and carried out for the damage simulation of asphalt mixture under the environmental effect of rain, high temperatures, and sunshine. Ultrasonic detection method is used to determine the ultrasonic velocity of asphalt mixture specimen under different temperatures and water contents in the process of water-temperature-radiation cycles. Thus, we get the preliminary damage assessment. Splitting strength attenuation is defined as the damage parameter. In addition, the regression prediction models of the ultrasonic velocity and damage coefficient of asphalt mixture are constructed using the grey theory, neural network method, and support vector machine theory, respectively. We compare the prediction results of the three different models. It can be concluded that the model derived from the support vector machine possesses higher accuracy and stability, which can more satisfactorily reflect the relationship between ultrasonic velocity and damage coefficient. Therefore, the damage degree of the asphalt mixture can be obtained.